1992
DOI: 10.1159/000236340
|View full text |Cite
|
Sign up to set email alerts
|

Airway Hyperresponsiveness is Associated with Inflammatory Cell Infiltration in Allergic Brown-Norway Rats

Abstract: The time course of the development of airway hyperresponsiveness (AHR) to inhaled acetylcholine (ACh) and the associated inflammatory cell recovery in bronchoalveolar lavage fluid (BAL) in actively sensitised Brown-Norway rats was studied following challenge with inhaled ovalbumin (OA). IgE for OA was detected in serum obtained from sensitised rats using passive cutaneous anaphylaxis, at titres of 1:10 to 1:30; none was detected in unsensitised animals. There was no significant change in either airway responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
23
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 11 publications
6
23
1
Order By: Relevance
“…The present authors wanted to assess the involvement of another Th2 marker, development of airway eosinophilia after allergen challenge. Possible attenuation of airway eosinophilia might have clinical importance, since some previous studies have found that airway eosinophilia is closely related to increased bronchial hyperreactivity [26], although this is not a constant finding [27]. However, infiltration of eosinophils into the airways 24 h after aerosol challenge with TMA-RSA was not attenuated in the group made tolerant to OvA in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…The present authors wanted to assess the involvement of another Th2 marker, development of airway eosinophilia after allergen challenge. Possible attenuation of airway eosinophilia might have clinical importance, since some previous studies have found that airway eosinophilia is closely related to increased bronchial hyperreactivity [26], although this is not a constant finding [27]. However, infiltration of eosinophils into the airways 24 h after aerosol challenge with TMA-RSA was not attenuated in the group made tolerant to OvA in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…These animals develop significant airway hyper-responsiveness to inhaled methacholine in response to OVA challenge. Hyper-responsiveness has been associated with increased BAL-derived CD4 + T cell numbers [27], increased inflammatory-cell influx [28], and increased Eo-associated IL-5 levels in BALF [29]. ICAM-1 is important in generation of hyper-responsiveness, which can be attenuated by treatment with anti-ICAM-1 antibody [30].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study is to further clarify the role of MIF in asthma using rats. The study will demonstrate that anti-MIF Ab inhibits ovalbumin (OA)-induced airway inflammation as well as airway hyperresponsiveness in Brown Norway rats, which have been used as a model of atopic asthma [15][16][17].…”
mentioning
confidence: 99%